Determination of Mean Blood Loss with Tranexamic Acid in Patients Undergoing Total Knee Arthroplasty: Mean Blood Loss with Tranexamic Acid Total Knee Arthroplasty Patients - Ali, Muhammad Asjad; Aslam, Shoaib; Saqlain, Syed Salman; Asif, Hafiz Salman; Iqbal, Muhammad; Aslam, Hafiz Muhammad Asad; Hameed, Sajid (Pakistan Journal of Health Sciences, 2025)
Orthopedic surgeons routinely perform total knee arthroplasty (TKA). The use of antifibrinolytic therapy is one of the strategies to manage perioperative bleeding. TXA works by occupying the lysine-binding sites on plasminogen, thereby hindering its attachment to fibrin and ultimately halting the fibrinolysis process. Blood loss during gynaecological, cardiac, and orthopedic surgeries can be effectively managed with tranexamic acid. Objectives: To determine the average reduction in blood loss achieved with tranexamic acid in patients undergoing total knee arthroplasty. Methods: This interventional study was conducted over six months, from 25-08-2020 to 25-02-2021. A total of 60 patients from the OPD of the Orthopedic Department at Mayo Hospital, Lahore, were included in the study based on selected criteria. All participants signed informed consent forms. Demographic data were recorded, and TXA was administered after the surgery. All procedures were performed under general anesthesia. Results: The analysis showed that the average blood loss during surgery was 255.14 ml with the use of tranexamic acid. Excessive blood loss can have detrimental effects on a patient’s health. Conclusions: It was concluded that tranexamic acid is effective in reducing bleeding during total knee replacement. Its use may also be more cost-effective compared to managing the consequences of significant blood loss.